Bradycardia and asystole during temporomandibular joint reconstruction. Issue 10 (29th August 2020) - Flannery, Kaitlin M.; Yu, Jason W.; Resnick, Cory M.; Evans, Faye M.
Abstract: Anesthesia providers are familiar with the oculocardiac reflex, one type of trigeminocardiac reflex. While less common, arrhythmias associated with manipulation of other trigeminal nerve branches can occur. We report the presentation and management of bradycardia and asystole from stimulation of the mandibular branch of the trigeminal nerve during temporomandibular joint reconstruction.